TINDAK TUTUR DIREKTIF GURU DAN SISWA DALAM PEMBELAJARAN DI KELAS III SDN TIPO PALU - Sumiatun, Sumiatun (BAHASANTODEA, 2016)
Language in the class learning activity is communication interaction reality which continuing. The teacher must be able to communicate, and manage the class with well to create learning atmosphere is fun and have the meaning for the student. In this research related with the directive teacher and student speech action. The problem which solved consist 3 matters, there are (1) The form, (2) and, (3) Directive teacher and student speech action strategy in the learning of the third grade student at SDN Tipo Palu ?. this research have the purpose to describe the using of directive action which consist (1) form, (2) function, and (3) Directive teacher and student speech action strategy in the learning of the third grade student at SDN Tipo Palu. The method which using is descriptive qualitative method. The data accumulation was done with two techniques, there are (1) recording and (2) observation. The research subject are teacher and the third grade student at SDN Tipo Palu. Data Analysis technique in this research is interactive model. Analysis in the research include 4 steps, there are (1). Data accumulation, (2) data reduction, (3) data presentation, and (4) verification/conclusion. The result of the research showing that in the larning of third grade student at SDN Tipo Palu, consist at the form : (1) Command, (2) statement, (3) question, (4) requesting, (5) prohibit. The function directive action which found at the result of the research consist by (1) command function, (2) statement function, (3) Question Function, (4) requesting function, and (5) Prohibit function. There are (1) command function is to do the other people to do something which desired. (2) statement function is functioned as give an information to the opponent speech. (3) the function of question sentence is to request the answer like an explanation to exhume an information, to clarify, or confirm. (4) request function is to request or prohibit someone to doing something. (5) the function of prohibit sentence is to prohibit people or a group of people to not doing something. The strategy which using in the directive action consist by direct strategy and indirect strategy. Directive speech strategy which many shows is speech action directive direct strategy. There is the speech action directive indirect at this research in the learning process of the third grade student at SDN Tipo Palu only two strategies, there are statement strategy and prohibit strategy, are (1) indirect strategy in the question, and (2) indirect strategy in the prohibit. There is direct strategy consist of : (1) direct strategy in the command, (2) strategy in the statement, (3) direct strategy in the question, (4) direct strategy in the requesting, and (5) direct strategy in the prohibit.Â